Analisis Kapasitas Galangan Kapal Ikan Untuk Memenuhi Rencana Pengadaan Kapal Ikan Hibah - Agus Lubis Fitriansyah; Heri Supomo (Badan Riset dan Inovasi Nasional, 2019)
The government through the Ministry of Marine and Fisheries offers assistance of fishing vessel to achieve fisheries production targets. This procurement plan must be supported by the ability and selection of the right shipyard. Beacuse the information of the capability and capacity of fiber shipyards in Indonesia is unclear, so the realization of the procurement of fishing vessel in previous years did not met the planned targets. The purpose of this study was to analyze shipyard capacity to meet the planned procurement of KKP fishing vessels grant in 2019. First classification of fishing vessels is based on the size of each GT, which is <5 GT (type 1), 5-10 GT (type 2), and 20-30 GT (type 3). The second is the minimum shipyard criteria for building fishing boats. Third, an assessment of the shipyard is based on the criteria that have been made. Fourth, shipyard selection was carried out on each WPPN-RI using the load score method. The fifth calculates the number of ships that can be built by the shipyard. The results of the shipyard assessment found that 43% of shipyards have the ability to build type 1 vessels, around 38% of shipyards have the ability to build type 2 vessels, and around 19% of shipyards have the ability to build type 3 vessels. is 1625 units / period. Referring to shipyard capacity, it can be said that the entire shipyard is able to fulfill the plan to procure assistance for KKP fishing vessels in the 2019 budget year.